Implementasi Sekolah Ramah Anak dalam Mewujudkan Nilai-Nilai Karakter Anak Usia Dini di RA Hidayah Tayu Kabupaten Pati - Yuliana, Ari; nashiruddin, ahmad (Tinta Emas: Jurnal Pendidikan Islam Anak Usia Dini, 2022)
Schools are expected to be able to provide a sense of security, comfort and fun for children, so that the learning process and results are maximized. But the facts on the ground show that students often get pressure and feel uncomfortable when going to school. Inappropriate school conditions and an uncomfortable environment cause children to be vulnerable to violence, both verbal and psychological. The aims of this study are (1) to determine the concept of realizing a child-friendly school based on early childhood character values ​​in RA Hidayah Tayu, Pati Regency, (2) to examine the implementation of child-friendly schools in RA Hidayah Tayu, Pati Regency in realizing the character values ​​of early childhood. This study uses a qualitative approach with a descriptive method. The data sources used are primary data sources and secondary data sources. The data collection used are observation, interview and documentation techniques. Data analysis in this study used data collection, data reduction, data presentation, and drawing conclusions (verification). The results of the study show that RA Hidayah has implemented 4 child-friendly school concepts. The concept of a child-friendly school is carried out with the stages of preparation, planning, implementation and outcome (characterized students). While the implementation towards child-friendly schools is realized by the presence of 4 components, namely protection, care, education and health.